INNOVATION IN THE MANAGEMENT OF ISLAMIC EDUCATION CURRICULUM: PERSPECTIVES AND IMPLEMENTATION - Loso Judijanto; Akib Akib; Risnawati Risnawati (Jurnal Ilmiah Edukatif, 2024)
Innovation in the management of Islamic education curriculum is an important effort to update and align the educational process with the needs of an increasingly dynamic era. This research examines the perspectives and implementation of such innovations, highlighting the importance of a contextualised approach that considers the needs of learners as well as the relevance of Islamic teachings in the modern context. The research findings show that the success of the innovation depends not only on improving teaching materials, but also on teaching methods that encourage students' active participation and enhance their understanding in technology and global competence. However, the implementation of this innovation faces challenges such as limited resources and resistance to change. Overcoming these obstacles requires collaboration between educational institutions, communities and support from governments and organisations. Thus, innovation in the Islamic education curriculum can play an important role in shaping a generation that is strong in faith and adaptive and competent in facing global challenges.